2001
DOI: 10.1034/j.1399-0039.2001.580614.x
|View full text |Cite
|
Sign up to set email alerts
|

CD antigens 2001

Abstract: The most recent Human Leucocyte Differentiation Antigen Workshop ("HLDA7") took place in 2000 in Harrogate, UK and the proceedings are about to be published (Leucocyte Typing VII). New Sections were introduced in this Workship (Dendritic cells, Stem/progenitor cells, Erythroid cells and Carbohydrate Structures) and monoclonal antibodies were selected for which at least some molecular data were already available (to avoid "blind" screening of reagents against known specificities). A total of more than 80 new CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The antibodies most commonly used in diagnostic hematopathology are briefly described below. Additional information about each cluster of differentiation can be found at ''Protein Reviews on the Web,'' a web site maintained by the National Cancer Institute, and in numerous books and literature reviews (92)(93)(94)(95)(96)(97)(98).…”
Section: Basic Principles Of Immunophenotypic Analysismentioning
confidence: 99%
“…The antibodies most commonly used in diagnostic hematopathology are briefly described below. Additional information about each cluster of differentiation can be found at ''Protein Reviews on the Web,'' a web site maintained by the National Cancer Institute, and in numerous books and literature reviews (92)(93)(94)(95)(96)(97)(98).…”
Section: Basic Principles Of Immunophenotypic Analysismentioning
confidence: 99%
“…In addition, this initiative has not only assisted clinicians worldwide in diagnosis and therapy by providing independent confirmation of antibody specificity, but also has resulted in a universal nomenclature scheme [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies demonstrated that a chemokine, stromal cell-derived factor-1 [SDF-1, also termed CXCL12 according to a new classification system (Zlotnik & Yoshie, 2000)], plays a key role in the trafficking and homing of CD34 + cells to the marrow (Wright et al, 2002). SDF-1 induces HSC (Kim & Broxmeyer, 1998;Imai et al, 1999;Jo et al, 2000) and acute myeloid leukaemia (AML) cell migration (Mohle et al, 1998;Voermans et al, 2002) in vitro by binding to a G-protein-coupled receptor, termed CXCchemokine receptor R4 (CXCR4) that was designated CD184 during the most recent Human Leucocyte Differentiation Antigen Workshop (Mason et al, 2001). HSC are highly selective in their migratory response to SDF-1 (Wright et al, 2002).…”
mentioning
confidence: 99%